Designing countrywide and regional microclimate networks. Issue 6 (25th March 2021) - Lembrechts, Jonas J.; Lenoir, Jonathan; R. Scheffers, Brett; De Frenne, Pieter
Abstract: Issue: Climate change, and its impacts on ecological, agricultural and other societal systems, is most often studied by relying on temperature data derived from countrywide weather‐station networks. Yet, these data do not capture microclimates, those arising from soil, vegetation and topography, at spatial scales relevant to the majority of organisms on Earth. We argue that a unified strategy is missing to design regional or countrywide networks to measure microclimates and thus provide ecologically relevant and sound climate data, for instance for modelling biodiversity and ecosystem functions. Evidence: Here, we develop an integrative framework to design effective microclimate networks for potential implementation at the country level. With the dawn of novel low‐cost sensor technologies and modelling techniques it is time for designing standardized microclimate networks. We make an important step forward in that regard by providing hands‐on training to generate an optimal sensor distribution to capture as much microclimate diversity as possible at the regional or country scale. Conclusions: By implementing our framework to design countrywide or regional microclimate networks, strategically positioned to capture a representative picture of microclimates available within the focal country or region, governments could lay the foundation for the development of a next generation of modelling and synthesis of landscapes, to serve a range of societal needs now and into the future as climate change accelerates.